KUALITAS PELAYANAN BIDANG AKADEMIK TERHADAP KEPUASAN PELANGGAN UNIVERSITAS ISLAM “45” BEKASI - Neneng Fauziah; Rani Intan; Syahyono -; Ratna Emaliah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2021)
This study aims to analyze the effect of academic service quality on customer satisfaction at Unisma Bekasi and the application of Standard Operating Procedures (SOP) for academic services using descriptive quantitative research methods, with research respondents being all lecturers as users of academic services. Respondents became the research sample as many as 100 people collected 76 people. The data collected in this study consisted of primary data and secondary data. Based on the results of the research, it is necessary to carry out several things training to communicate and provide good service, excellent service training, archive management training, making standard operating procedures (SOPs) for education staff about services, socializing and implementing standard service procedures SOPs, giving awards to educational staff who provide good service.